Use of input necessary assignments for test generation based on merging of test cubes. Issue 2 (1st March 2015) - Pomeranz, Irith
Abstract : A class of test generation procedures achieve test compaction by merging of compatible test cubes. The number of tests is reduced when two test cubes, c 0 and c 1, are merged and replaced by a single test cube. In addition, the merging of c 0 and c 1 may result in the accidental detection of faults that are not detected by c 0 or c 1 alone. This can be used for speeding up the test generation process. This study enhances the likelihood of accidental detection by incorporating into the test cube merging process test cubes that represent input necessary assignments of target faults. Before generating a test cube for detecting a fault, merging of its input necessary assignments with other test cubes may result in the accidental detection of the fault. Experimental results for benchmark circuits demonstrate that this effect is significant in reducing the number of faults for which test generation needs to be carried out, thus speeding up the test generation process.